THE PRACTICALLITY OF PO2E2W LEARNING MATERIAL MODEL ASSISTED PHET MEDIA TO IMPROVE THE STUDENTS PHYSICS PROBLEM SOLVING SKILLS - Dian Sari, Agung Suci; Munasir, Munasir; Jatmiko, Budi (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
PO2E2W learning model (problem orientation, observation, explanation, elaboration, and write in science) assisted by PhET media is a learning model that is oriented towards self regulated learning which in the process of physics learning activities is carried out with the help of PhET media. The purpose of this study was to analyze the practicality of the PO2E2W model assisted by PhET media in improving the physics problem solving skills of high school students. This research was carried out at Kemala Bhayangkari 1 High School (Surabaya, Indonesia) for students of class XI IPA 1, XI IPA 2 and XI IPA 3. Criteria for practicality of learning devices in this study were based on (1) the implementation of the learning implementation plan (RPP) during one meeting in class XI IPA 1 and the implementation of the learning plan (RPP) for five meetings in class XI IPA 2 and XI IPA 3, (2) obstacles during learning activities. The number of observers in this study is two observers. The aspects observed consisted of introduction, core and closing activities. Based on the results of the practicality study of the PO2E2W model assisted by PhET media, the results obtained (1) the average assessment of two observers in class XI IPA 1 was 3.30 with good category with a percentage of agreement 96.75%, XI IPA 2 was 3.71 in very both with a percentage of agreement 95.84% and in class XI IPA 3 was 3.76 in very good category with a percentage of agreement 96.85% (2) obstacles during learning activities that can be overcome properly. Conclusion based on the results of the study of the freeness of the PO2E2W model assisted by PhET media is practically applied in learning to improve the physics problem solving skills of senior high school students.